Safety feature in installation Industrialized Building System (IBS) component / Syed Muhamad Jefri Syd Hamid - Syd Hamid, Syed Muhamad Jefri (Faculty of Architecture, Planning and Surveying, 2013)
Industrialized Building System (IBS) is one of the technologies which can be categorized long-standing technology in developed countries. IBS is a technique whereby components are manufactured in a controlled environment, either at site or off site and transported, positioned and assembled into construction work. IBS is also known as prefabricated, modem method of construction (MMC) and off-site construction. There are five categories of the IBS normally used in Malaysia which are precast concrete framing, panel and box systems, steel formwork system, prefabricated timber framing systems, and block work systems. Precast concrete is one of the main IBS category built in Malaysia since 1960s. The purpose of this study is to provide a general perspective of safety in precast concrete construction by achieving specific objectives which are study and investigate the best process of installation of IBS components at site and to study the safest method of IBS. The data were collected from three different case studies around Klang Valley. Some data from journal, articles, newspaper, and internet source also been used to support the research. The data that gathered from the case studies will be analyze and some data from the interview also been used. This study also can provide knowledge to contractors and workers about the safety aspect during installation of precast concrete components thus will decrease the percentage of accident and giving the high quality management of a construction project in the future.